"Tourist" Arts in Africa and Western Consumers: the case of Arts and Crafts in Niger - (:unkn) unknown (My University, 2009)
« Tourist » Art is a form of commercial art distributed in a host country intended to tourists consummation and giving a stereotype image about the visited country and its nation. That we call African “Tourist” Art dissent from Western Tourist Art in three points: First it is essentially a local production, usually made by little production structures as workshop. So the producer of African “tourist” items can often meet the foreign buyer and consequently he can question him in order to try to identify the consumer's tastes and expectations. In this symbolic aesthetic exchange, the foreign buyer participates to introduce new materials, forms and technology inside the items creation. Secondly, items originally from this exchange are hybrids because they are influenced by foreigners' tastes, foreigners who are in large majority Western people; this is the last specificity, but, these Western consumers whom have officious been identified by specialists of this subject as “tourists” are not only travellers in transit but expats and consumers from West too. Thus, the African “Tourist” Arts can not be considered as a tourist tastes revealing and consequently interesting only tourism sociologic problematic but they must be considerate as a telling about the link between West and the rest of the world.
Keywords: African Research